2005
DOI: 10.1016/s0002-9440(10)62996-3
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Plasminogen Activator System in Inflammation and Neurodegeneration in the Central Nervous System during Experimental Allergic Encephalomyelitis

Abstract: Early signs of inflammatory demyelination include entry of fibrin(ogen) into the central nervous system (CNS), which is normally excluded by the blood-brain barrier, and up-regulation of components of the plasminogen activator system. Using mice deficient in tissue-type plasminogen activator (tPA ؊/؊ ) and urokinase plasminogen activator receptor (uPAR ؊/؊ ), we investigated the involvement of the PA system on the clinical and pathological features of experimental allergic encephalomyelitis, an animal model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 56 publications
(56 reference statements)
9
61
0
Order By: Relevance
“…A delay in neuroinflammation accompanied by a higher capacity for fibrinolysis resulted in a milder disease in PAI-1 -/-mice with no clinical relapses or recurrent neuropathology. In contrast, immunocytochemistry of representative spinal cord samples from WTs had a similar disease pattern to mice of the pure ABH strain [13] with marked inflammation, impairment of fibrinolysis, focal demyelination and axonal degeneration, confirming results in our recent report [1].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A delay in neuroinflammation accompanied by a higher capacity for fibrinolysis resulted in a milder disease in PAI-1 -/-mice with no clinical relapses or recurrent neuropathology. In contrast, immunocytochemistry of representative spinal cord samples from WTs had a similar disease pattern to mice of the pure ABH strain [13] with marked inflammation, impairment of fibrinolysis, focal demyelination and axonal degeneration, confirming results in our recent report [1].…”
Section: Discussionsupporting
confidence: 89%
“…In control WT and PAI-1 -/-mice, myelin staining was dense and complete in the white matter of the spinal cord (not shown, as per our prior report [1]). There were no differences in MBP staining between the genotypes at any stage of CREAE, except at 40 dpi, where PAI-1 -/-mice were still in disease remission and had normal appearing myelin staining while WTs were relapsing and had some evidence of demyelination in the spinal cord, specifically in areas of perivascular inflammation with macrophage infiltration (Figure 2G,H).…”
Section: Inflammation and Demyelinationsupporting
confidence: 84%
See 2 more Smart Citations
“…Using mice deficient in tissuetype plasminogen activator (tPA-/-), East et al investigated the involvement of the PA system on the clinical and pathological features of EAE. They found that tPA-/-mice suffered an early and a more severe acute disease characterized by incomplete recovery when compared to wild-type controls [6]. A better understanding of the mechanism of inhibition of coagulation-fibrinolysis system facilitate disease pathogenesis may present a new strategy for pharmacological intervention in inflammatory demyelinating diseases.…”
Section: Discussionmentioning
confidence: 99%